STRATEGI PENGEMBANGAN DANAU EMBULAN SEBAGAI DESTINASI WISATA Di DESA AIK BUKAQ KECAMATAN BATUKLIANG UTARA LOMBOK TENGAH - Nuri Dahlan; I Made Murdana; Ajuar Abdullah; I Putu Gede; Lalu Masyhudi (Journal Of Responsible Tourism, 2022)
The problems studied in this study are related to the development of potential tourist attractions owned by Embulan Lake as a Tourist Destination and to formulate development strategies that are in accordance with environmental conditions. The method used in this research is descriptive qualitative by using data collection techniques in the form of observation, interviews, and documentation, while to analyze the data the researcher uses SOAR analysis. The results of this study are Embulan Lake has a potential tourist attraction that can be developed as a tourist destination, while the Embulan Lake development strategy is as follows: Development of natural tourism potential such as water tourism, educational tourism, Cultural tourism development such as storytelling, Development of supporting facilities, Capturing linkage with travel units (travel agents), Collaborating between academics in the tourism sector, Creating a management agency from the Petikus Daye Hamlet community which will be under the auspices of the central pokdarwis in Aik Bukaq Village, Preparing existing business units (UMKM), implementation of concept of CBT, Conducting promotions, Collaborating between existing tourist destination managers, Creating official accounts on social media, Conducting durian fruit events at Embulan Lake.